THU0206 А VERY EARLY (7-28 DAYS) RESPONSE ON JAK INHIBITOR TOFACITINIB IN PATIENTS WITH ACTIVE RHEUMATOID ARTHRITIS: EFFECT ON PAIN AND CENTRAL SENSITIZATION. (13th June 2020) - Karateev, A.; Filatova, E.; Pogozheva, E.; Amirdzhanova, V.; Nasonov, E.; Lila, A.; Mazurov, V.; Lapkina, N.; Lukina, G.; Salnikova, T.; Samigullina, R.; Chakieva, D.; et al.
Abstract : Background: The presence of central sensitization (CS) significantly burdens the course of rheumatoid arthritis (RA). JAK inhibitors block intracellular signal pathways including the ones responsible for synthesis of mediators and cytokines causing pain and CS. The application of JAK inhibitors is supposed to relieve pain and reduce CS severity promptly. Objectives: To evaluate JAK inhibitor effect on pain and signs of CS in patients with active RA 7 and 28 days after the start of therapy. Methods: Study group included 39 patients with RA, their age was 50.9±11.1, 79.5% of women, 89.7% of RF "+", DAS28 5.8±0.6, receiving DMARDs (methotrexate 82.0% and leflunomide 18.0%), who were administered with tofacitinib 5 mg 2 times a day due to inefficiency or intolerance of genetically engineered biological drugs. There were assessed the pain severity using Brief pain inventory (BPI) questionnaire, the presence of neuropathic pain component (NPC) using PainDETECT questionnaire and signs of CS using Central Sensitisation Inventory (CSI) questionnaire at early time after tofacitinib administration. Results: Patients initially experienced a severe pain – 5.72±2.21 according to the visual analogue scale (VAS), 53.8% had signs of central sensitization (CSI ≥ 40), 17.9% had NPC (PainDETECT ≥18). 7 days after tofacitinib intake there was statistically reliable reduction of pain severity – up to 4.37±2.2 (р=0.01), pain decrease of 29.4±17.9% (BPI), NCP – PainDETECT from 12.9±5.5 to 10.6±5.6 (р=0.047) and CS – CSI from 43.1±12.8 to 35.9±11.2 (р=0.01). The effect had increased after 28 days: pain level (VAS) was 2.84±1.57 (р=0.000), pain decrease of 43.6±29.6% (BPI), PainDETECT 29.8±12.4 (р=0.000), CSI 26.4±13.9 (р=0.000). During this period there were no serious adverse reactions. Conclusion: The application of JAK inhibitor tofacitinib allows to reach a fast analgesic effect, also due to impact on CS and NCP. Source: National Registry patients with RA Disclosure of Interests: Andrey Karateev: None declared, Ekaterina Filatova: None declared, Elena Pogozheva: None declared, Vera Amirdzhanova: None declared, Evgeny Nasonov: None declared, Alexander Lila: None declared, V Mazurov: None declared, N Lapkina: None declared, Galina Lukina Speakers bureau: Novartis, Pfizer, UCB, Abbvie, Biocad, MSD, Roche, Tatiana Salnikova: None declared, Ruzana Samigullina: None declared, Diana Chakieva: None declared, Irina Marusenko: None declared, Olga Semagina: None declared, Marina Semchenkova: None declared